Determination of leakage from antibody adsorbent: composition analysis and pH effect. (17th May 2013) - Zhao, Lan; Liu, Yongdong; Wang, Yinjue; Huang, Yongdong; Li, Xiunan; Li, Yan; Ma, Guanghui; Su, Zhiguo
ABSTRACT: To study the leakage at different solution pH values, IgG Sepharose 6FF®, a commercially available immunoadsorbent, was used as a model. The leaked substance consists of three parts: (1) ligands and its fragments; (2) ligands plus matrix fragments in which ligands are chemically attached to the adsorbent matrix; and (3) matrix fragments. Buffer solution pH values had a great effect on both the kinetics and the amount of ligand leakage. Cross‐linking of the adsorbent matrix could reduce both matrix leakage and antibody leakage at pH 3.0, but its effect was limited at pH 11.0 for ligand leakage. Copyright © 2013 John Wiley & Sons, Ltd.